Influence of deoxidizing powder on the internal surface of hot-rolled pipes - O. V. Rozhkova (Литьë и металлургия)
The article describes the experience of using deoxidizing powder in the technological process of production of hot-rolled seamless pipes; the processes that occur when applying to the inner surface of the hollow billet deoxidizing powder. The results of experimental and industrial tests of deoxidizing powder of different chemical composition are presented. The influence of the chemical composition of the deoxidizing powder on the formation of defects on the inner surface of the pipes is shown. Describes the stages of metallographic analysis of the defects on the inner surface of the pipe, provided the reasons for the formation of the defect «pipe rolling lap (skin)».